Perbandingan Kualitas Air di Pulau Jawa dan Kalimantan (Review Jurnal) - Yuliani, Rida; Imaningsih, Witiyasti (Jurnal Farmasi (Journal of Pharmacy), 2020)
A review of water quality from the results of research on Java and Kalimantan has been carried out to get an illustration of water contamination level (refill drinking water, PDAM water, and well water) by Coliform bacteria. Data was obtained from secondary sources of research results from several regions in Java and Kalimantan. The results of water quality assessment of the two islands are presented as a percentage. Based on the results, the level of water contamination on Java island is higher than Kalimantan. The average percentage of Coliform contamination in water on Java is 61.42% and only 42.26% in Kalimantan. The high percentage of water contamination by Coliform bacteria in Java is due to the fact that Java has a higher source of contaminants. The existence of Coliform sources was influenced by the population, housing, and organic waste production.